Política e racionalidade no processo decisório de alocação de recursos: o caso da Universidade Federal de Santa Maria - Camponogara, Fernando Bevilaqua (2017)
The subject of study is the politics and rationality in the decision-making process for financial resources’ allocation. The main objective was to identify the influence of these factors on the actions of public managers, when faced with the financial shortage scenario experienced at the Federal University of Santa Maria (UFSM) during the financial year of 2015. The relevance of the present study is in its proposal of consider the procedures of resource allocation in the UFSM in view of the factors involved in this process, which aims to meet the needs of society. The unit of analysis defined for this research was the Prorectorate for Administration and the departments under its coordination. Therefore, it was chosen the case study in which the decision-making process was analyzed from different angles, having as theoretical reference the rational, organizational and political models. For the study, the rational and the organizational models were simultaneously treated as rationality for the purpose of its delimitation, reducing the analysis to the rational perspective and to the politics concerning decision-making. The methodological procedures employed were of exploratory type, with a qualitative approach, and the data collected were obtained from different sources of evidence, using documents, observations and semi-structured interviews with public managers who acted in resource allocation decisions. The content of the interviews was examined using the thematic and categorical type of content analysis, based on the analytical categories initially proposed. The obtained results revealed the complexity of the decision-making process as studied, and the analysis showed that rationality factors and political factors concomitantly influenced the decision of financial resource allocation. The theoretical factors of rationality identified as influencers in the decision process studied were: rational choice, bureaucratic rationality, limited rationality and organizational structure and processes. Among these factors, the rational choice was shown less clearly than the other factors. The political factors identified were: negotiation, power, conflict, coalition, interests and external influence. The rational character of the decision-making process in resource allocation was present both in the distribution and in the formalization of typical administrative processes of bureaucratic organizations. The political dimension was evidenced in the phase that comprised the resource allocation decision, properly speaking, since that happened in the midst of a complex social process in which rational aspects were interrelated with political components, which originate from the multiplicity of interests and approaches by the managers involved.